2013
DOI: 10.1099/vir.0.052126-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Leader protein coding region of foot-and-mouth disease virus on virus replication

Abstract: The foot-and-mouth disease virus (FMDV) Leader (L) protein is produced in two forms, Lab and Lb, differing only at their amino-termini, due to the use of separate initiation codons, usually 84 nt apart. It has been shown previously, and confirmed here, that precise deletion of the Lab coding sequence is lethal for the virus, whereas loss of the Lb coding sequence results in a virus that is viable in BHK cells. In addition, it is now shown that deletion of the ‘spacer’ region between these two initiation codons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…It is well known that interferon has a strong inhibitory effect on FMDV replication and studies have shown that expression of interferon, from adenovirus vectors, can effectively block FMDV replication in swine. 71 The precise deletion of the Lb coding region to make a socalled "leaderless virus" (see Figure 4) from FMDV results in a virus which is still viable [72][73][74] but attenuated in cattle. 75 The loss of Lb results in a decreased ability of the virus to shut off host cell protein synthesis; this will allow the synthesis of interferon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that interferon has a strong inhibitory effect on FMDV replication and studies have shown that expression of interferon, from adenovirus vectors, can effectively block FMDV replication in swine. 71 The precise deletion of the Lb coding region to make a socalled "leaderless virus" (see Figure 4) from FMDV results in a virus which is still viable [72][73][74] but attenuated in cattle. 75 The loss of Lb results in a decreased ability of the virus to shut off host cell protein synthesis; this will allow the synthesis of interferon.…”
mentioning
confidence: 99%
“…75 The loss of Lb results in a decreased ability of the virus to shut off host cell protein synthesis; this will allow the synthesis of interferon. 76 Such viruses can grow well in BHK cells 73,74 and may represent useful tools for the development of safer vaccine strains for conventional cell culture production since any escape only releases viruses that are non-pathogenic and cannot revert to virulence. There has been significant interest recently in generating marked FMDVs which may permit improved DIVA and/ or offer alternative routes for virus purification.…”
mentioning
confidence: 99%
“…The length and secondary structure of La are conserved, while the nucleotides are highly variable (10). Furthermore, previous studies have demonstrated that La is involved in viral replication (7,30). L pro is a papain-like protease (20,32,38), and its two forms exhibit similar proteolytic activities (27,39).…”
Section: Introductionmentioning
confidence: 97%
“…However, mutation of the Lb AUG abolishes virus viability (Cao et al, 1995). The region between the two AUGs named 'spacer' region seems to be essential for some activity unrelated to its coding function, although deletion of the Lab 'spacer' region generates a functional Lb protease (Belsham, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This cleavage can also take place in trans. Construction of FMDVs with truncated L proteins showed that infectivity required that the residues that encode the N-terminus of VP4 be positioned directly following the second functional Lb AUG codon (Belsham, 2013;Piccone et al, 1995a), and the virus displayed reduced fitness. The deletion of the entire Lab-coding sequence with the Lab AUG positioned before the N-terminal Gly of VP4 resulted in a non-viable virus (Piccone et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%